12-9 Pemberton Square, ca. 1885 - J. W. Black & Co. (Tufts Archival Research Center, 2005)
Street-level view west of (left to right) 12-9 Pemberton Square. The facades of the dwellings face east. The southwest corner of 8 Pemberton Square is included along the right side of the photograph. A horse-drawn carriage is visible in the lower-right corner of the photograph. 4 5/8 x 7 3/4, 5 1/4 x 8 1/2 overall Cabinet photographs